PERSEPSI ANGGOTA TENTANG MANFAAT KOPERASI SIMPAN PINJAM SYARIAH BMT UGT SIDOGIRI DESA SUNGAI AMBAWANG - Annisa, Cici Nurul; Parijo, Parijo; Aminuyati, Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this thesis is "Members 'Perceptions About the Benefits of Cooperatives for Members' Welfare in Syariah Savings and Credit Cooperatives BMT Sidogiri UGT in Sungai Ambawang Village". This study aims to determine members' perceptions about the benefits of Syariah Savings and Loans Cooperative BMT Sidogiri UGT Sungai Ambawang Village. The form of research used is a survey study. With members of the Syariah Savings and Loan Cooperative BMT Sidogiri UGT Sungai Ambawang Village as resource persons and 5 members as respondents. The method used is descriptive method with the aim to describe objectively the members' perceptions about the benefits of Syariah Savings and Loans Cooperative BMT Sidogiri UGT Sungai Ambawang Village. Using data collection tools are direct communication techniques, documentary study techniques, interviews, and notes. While the data processing is doing descriptive analysis. These results state that members' perceptions about the benefits of the Syariah Savings and Loans Cooperative in Sidogiri UGT Sungai Ambawang Village are positive, means that the benefits of the cooperative are felt and made a positive contribution to the members and are able to become an institution that can prosper the members.Â Keywords : Member perceptions, cooperative benefits, and member welfare